Regional Dynamics in a Decentralized Indonesia - Hill, Hal, 1948- (Book collections on Project MUSE., 2014)
Indonesia is the world's largest archipelagic state. In 2001 it embarked on a "big bang" decentralization involving a major transfer of administrative, political and financial authority to its districts, now numbering more than 500. Together with the rapid transition from authoritarian to democratic rule in the late 1990s, this initiative has transformed the country's political, social and business life. While national government is the major area of contestation, power has shifted irreversibly away from the centre. How this significantly increased regional autonomy works will have a crucial bearing on the future of the Indonesian nation-state. This volume features contributions by over 40 writers with deep expertise on Indonesia. The book provides a timely, comprehensive and analytical assessment of the country's regional development dynamics in the post-decentralization environment. It explores historical, political and development patterns at the regional level; the relationship between decentralization and governance; local-level perspectives; migration, cities and connectivity; and the challenges confronting the peripheral regions of Aceh and Papua